PENGARUH SUMBER INFORMASI TERHADAP PERILAKU PENGGUNAAN OBAT SAAT MENJALANI ISOLASI MANDIRI COVID-19 DI KOTA DENPASAR - Suryaningsih, Ni Putu Aryati; Rinata, Ayunda Deva (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Coronavirus disease 2019 (COVID-19) is a global pandemic with a very rapid rate of spread. As of June 2021, Bali Province experienced an increase in the number of weekly cases by 110%. The sharp increase caused referrals for self-isolation to also increase. The increase in referrals for COVID-19 self-isolation also increases the tendency for diverse community drug use behavior. The behavior of drug selection and use carried out by respondents is related to the level of knowledge of respondents from previous prescriptions, information circulating in the environment and the media. Sources of information are considered to influence the behavior of drug use formed while undergoing COVID-19 self-isolation so that it is necessary to conduct this study. Research Objectives: This study aims to determine the effect of information sources on the use of drugs formed while undergoing COVID-19 self-isolation. Methods: The research design used was descriptive quantitative with a cross sectional research design. The number of samples used was 102 respondents with purposive sampling. Measurements were made using a questionnaire with data analysis techniques Univariate Test and Multivariate Binner Logistic Regression. Results: sociodemographics of respondents aged between 26-45 years 49%, and married as much as 57.8% dominated by female respondents 53.9%, the majority as private employees and civil servants 33.3% with a history of secondary education 61.8% and the majority of high income 55.21%. The people of Denpasar City who have positive drug use behavior 58.8% and who have negative drug use behavior 41.2%. It was found to have a significant influence (p=0.009) on drug use behavior while undergoing COVID-19 self-isolation. Conclusion: People in Denpasar City who have undergone COVID-19 self-isolation are classified as having positive drug use behavior. Information sources have a significant influence on drug use behavior while undergoing COVID-19 self-isolation.